Genetic variability in response to clopidogrel therapy and its clinical implications - Yukhanyan, Liana; Freynhofer, Matthias K.; Siller-Matula, Jolanta; Schrör, Karsten; Huber, Kurt (Thrombosis and Haemostasis, 2011)
This article concentrates on individual genetic differences responsible for variations of action of clopidogrel, which have been found to be partially responsible for increased cardiovascular events in patients with coronary artery disease under dual antiplatelet therapy. According to these results, genotyping for the relevant gene polymorphisms, especially for the CYP2C19 loss-of-function alleles, has been discussed to be an effective method of individualising and optimising clopidogrel treatment. However, due to the facts that 1) there are no prospective studies demonstrating a clinical benefit of personalising antiplatelet therapy based on genotyping; 2) CYP2C19 polymorphisms account for only approximately 12% of variability in clopidogrel platelet response; 3) the positive predictive value of CYP2C19 loss-of-function polymorphisms for cardiovascular events in patients with acute coronary syndrome undergoing percutaneous coronary intervention is only approximately 12% – 20%; 4) it is likely that other clinical factors and risk constellations might be of greater clinical importance; and 5) it is unknown whether a specific genetic polymorphism is capable of influencing outcome for the individual patient; genetic profiling cannot be recommended for routine use at present but will remain of considerable scientific interest.
Keywords: Antiplatelet agents; coronary syndrome; gene mutations; thrombosis